O ritual e os símbolos: a realização dos grafismos rupestres na região do município de Camalaú (PB) - Duarte, Patrícia (2011)
This work aims to infer the relationship between the realm of myth with the production of rock graphics, ie, whether the production of these graphics are rituals linked to a mythic structure whatever, being able to express a sacred dimension. Through authors such as Eliade (1991, 1983, 2007, 2008 a, 2008 b), Leroi-Gourhan (2007), Levi-Strauss (1996, 2007, 2008), Insoll (2004), Martin (2005), among others we seek to build a theoretical framework that provides a support for the possibility of discussions undertaken between the expressions of relational cave rituals and actions that produced them. In this paper we seek to support this theme in the theoretical overview presented by the authors that were the basis for discussing the question of sacred and ritual in the theoretical universe of Archaeology. As the focus of the research was chosen the Cariri Region, in the west of the state of Paraíba, especially the municipality of Camalaú, where the two sites were analyzed. To reach the objectives proposed in this study, we used two sites: the site Roça Nova and Beira Rio both fit the requirements established by the work because they have elements where the representations linked to the Traditionin the northeast standout, interspersed with elements of the tradition of the Agreste. It was possible to establish hypotheses of relationship that we set out to do. Using a comparative methodology and, a qualitative, we used the typological method to make comparisons between the two sets of signs of the sites. Aggregated data were collected from the contexts of insertion sites, topography, environment and spatial relationship with the water. Thus, we could demonstrate that the rite of producing rock graphics in each of the sites seem to indicate that the mythic structures vary according to the combination of graphics, distribution and typology, forms the supports with a possible relationship with other topography and ritual sites chosen at each site, even with the similarities between the proximity of the water and the techniques which they represent. Although it is not possible to identify a mythological arrangement in these sites at this time, it is demonstrated that it deals with completely different ritual moments. This leads one to suppose that this deals with a mythical structure for each group.